2000
DOI: 10.1002/1097-4644(20001101)79:2<282::aid-jcb110>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenite on estrogen receptor-? expression and activity in MCF-7 breast cancer cells

Abstract: To determine whether selenite has estrogen-like activities, the effects of this compound on estrogen receptor-alpha (ER-alpha) and other estrogen-regulated genes were measured in the human breast cancer cell line MCF-7. Treatment of cells with 1 uM of sodium selenite resulted in a 40% decrease in the amount of estrogen receptor-alpha and in a parallel decrease of 40% in ER-alpha mRNA. Progesterone receptor concentration increased 2.6-fold and pS2 mRNA increased 2.4-fold after selenite treatment. The induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Studies in MCF-7 cells have shown that Se, in the form of sodium selenite, binds to the hormone-binding domain of the estrogen receptor resulting in its subsequent activation (Stoica et al, 2000b). Exposure to Se has also been shown to increase the transcription of the progesterone receptor.…”
Section: Seleniummentioning
confidence: 99%
“…Studies in MCF-7 cells have shown that Se, in the form of sodium selenite, binds to the hormone-binding domain of the estrogen receptor resulting in its subsequent activation (Stoica et al, 2000b). Exposure to Se has also been shown to increase the transcription of the progesterone receptor.…”
Section: Seleniummentioning
confidence: 99%
“…Replacement of zinc in the zinc finger of ER with either nickel or copper could inhibit the binding of the DNAbinding domain of the ER to the ERE in the DNA [50]. Cadmium [51], arsenite [52], selenite [53], copper, cobalt, nickel, lead, mercury, tin, chromium and vanadate [54] can all interfere with oestradiol binding to the ligand binding domain of the ER and influence oestrogen-regulated gene expression. Furthermore, oestrogenic affects of cadmium have also been demonstrated in vivo in the rodent uterus and mammary gland [55].…”
Section: Aluminium and Oestrogen Actionmentioning
confidence: 99%
“…Inorganic selenite is reported to interact with the ligand binding domain of ERa and activate ERa transcriptional activity (29). To determine whether MSA altered estradiol binding to ERa, whole cell ligand binding assays were done in MCF-7 cells.…”
Section: Msa Potentiates the Growth Inhibitory Properties Of 4-hydroxmentioning
confidence: 99%